2017
DOI: 10.1590/s1980-6574201700020005
|View full text |Cite
|
Sign up to set email alerts
|

Project PANK: Rationale, study protocol and baseline results of a multidisciplinary school based intervention in children with cardiovascular and metabolic risk factors

Abstract: -Aims: Cardiovascular disease risk factors occur more frequently in children with obesity. Project PANK is a multidisciplinary school-based intervention lasting 6 months to improve BMI z-score, waist circumference (WC), waist-to-height ratio (WHtR), blood pressure (BP), nutrition, physical activity (PA), sedentary behaviour (SB), cardiorespiratory fitness (CRF), glucose, cholesterol, and triglycerides (TG). Methods/Design: A total of 77 children (7-10 years) were recruited from an urban school. The protocol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…There was no relationship between total sedentary time and levels of insulin, 35,36,40,43,52,53,56 glucose, 25,31,35,36,40,43,50,52,53,56,58 , and insulin resistance 36,54,57,58 in the analyzed studies (Table 2). Only three studies showed a positive association between total sedentary time and each individual parameter (insulin, 58 glucose, 18 and insulin resistance 12 ).…”
Section: Sedentary Behavior and Insulin And Glucose Levelsmentioning
confidence: 90%
See 4 more Smart Citations
“…There was no relationship between total sedentary time and levels of insulin, 35,36,40,43,52,53,56 glucose, 25,31,35,36,40,43,50,52,53,56,58 , and insulin resistance 36,54,57,58 in the analyzed studies (Table 2). Only three studies showed a positive association between total sedentary time and each individual parameter (insulin, 58 glucose, 18 and insulin resistance 12 ).…”
Section: Sedentary Behavior and Insulin And Glucose Levelsmentioning
confidence: 90%
“…The data on lipid profile presented in Table 2 show that the majority of studies did not demonstrate an association between total sedentary time and levels of total cholesterol (TC), 18,43,50,56 high-density lipoprotein cholesterol (HDL-C), 18,25,31,35,36,43,50,52,56,58 low-density lipoprotein cholesterol (LDL-C), 18,43,50,52,56,58 very low-density lipoprotein cholesterol (VLDL-C), 43 non-HDL cholesterol, 22,32 TC/HDL-C ratio, 54,57 and triglycerides (TG). 25,31,35,36,40,50,[52][53][54][56][57][58] However, some studies indicated that children and adolescents with more sedentary time during the day had higher levels of TG 18,43 and LDL-C 53 and lower levels of HDL-C. 40,53 The analysis focusing on patterns of sedentary time showed that in most studies there was no relationship between bouts 22,32,…”
Section: Sedentary Behavior and Lipid Profilementioning
confidence: 99%
See 3 more Smart Citations